It's part of the job: How webcare agents regulate their emotions during service interactions on Facebook and Twitter. (June 2021) - Widdershoven, Svenja; Pluymaekers, Mark; Bloemer, Josée M.M.
Abstract: The current study investigates which strategies webcare agents employ to regulate their own emotions when interacting with customers through Facebook and Twitter. Gaining a better understanding of this is important, since (1) customers rely on their emotions when determining how satisfied they are with a service provider and (2) employees can only effectively influence customer emotions if they are able to keep their own emotions in check. By analyzing 'talk about emotion' from 17 semi-structured interviews with Dutch webcare agents, we discovered that they use a wide range of emotion regulation strategies (ERS), of which reappraisal is the most commonly mentioned one. An analysis of the use of first-person pronoun 'I', fourth-person pronoun 'you' and exclusive 'we' suggests that the implementation of emotion regulation strategies is supported by the professional role that webcare agents construct for themselves. Results show that webcare agents are generally not influenced by negative emotions, which they see as an inherent part of their job, arising from circumstances that fall outside their sphere of influence. In laying bare the emotion regulation process in the challenging context of webcare, the insights in this article may support webcare agents and their managers in developing a clear perspective on the role requirements and constraints.